1996
DOI: 10.1097/00006123-199611000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Accelerates the Loss of Epidermal Growth Factor? Receptor Genes Amplified As Double-minute Chromosomes in Human Glioblastoma Multiforme

Abstract: These studies suggest the potential use of low-dose hydroxyurea in the treatment of GBMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…[12][13][14][15][16]32,33 In NB, MYCN amplification is associated with increased growth potential and tumorigenicity whereas down-regulation of MYCN expression correlates with decreased proliferation and differentiation induction. 34 Moreover, MNA late-stage tumors very often are refractory to chemotherapy, at least in part because the MYCN oncogene up-regulates expression of the MRP and MDR1 multidrug resistance genes in neuroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16]32,33 In NB, MYCN amplification is associated with increased growth potential and tumorigenicity whereas down-regulation of MYCN expression correlates with decreased proliferation and differentiation induction. 34 Moreover, MNA late-stage tumors very often are refractory to chemotherapy, at least in part because the MYCN oncogene up-regulates expression of the MRP and MDR1 multidrug resistance genes in neuroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Agents such as hydroxyurea, to which MDR1 over-expressing cells exhibit little or no cross resistance, have been shown to promote elimination of extrachromosomally amplified MYCN gene from tumor cells. 32,33 Inclusion of such drugs in conventional regimens constitutes an as yet unexplored therapeutic option specifically targeting aggressive cancer cells in the 30% of tumors with MYCN oncogene amplification. …”
Section: Discussionmentioning
confidence: 99%
“…The accelerated expulsion of extrachromosomally amplified genes by HU has been shown by a number of other authors (Snapka and Varshavsky, 1983;Von Hoff et al, 1991;Christen et al, 1992;Canute et al, 1996). Although the molecular mechanism is only partially understood, it has been shown that HU stimulates the formation of micronuclei.…”
Section: Hu Effects On Mycn Amplified Neuroblastoma Cellsmentioning
confidence: 91%
“…Expulsion of amplified genes has been shown to be accelerated in several tumor cell lines by low concentrations of hydroxyurea (HU) (Snapka and Varshavsky, 1983;Von Hoff et al, 1991;Christen et al, 1992;Canute et al, 1996) and it has been shown that the elimination of extrachromosomally amplified MYC genes from human tumor cells reduces their tumorigenicity (Von Hoff et al, 1992). Recent work has revealed that cancer cells are also capable of undergoing replicative senescence via telomere shortening as well as of entering a senescence-like state by activation of cell cycle inhibitory pathways (Hwang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Such drug-induced loss of amplified genes was most frequently reported for the DNA replication inhibitors such as hydroxyurea (HU) at lower concentrations (50 to 150 M ) than those that completely stopped DNA replication (1 to 2 m M ). This HU treatment resulted in a copy number decrease of the amplified DHFR in hamster CHO cells [Snapka and Varshavsky, 1983;Nevaldine et al, 1999], amplified c-myc in human colorectal carcinoma COLO 320DM cells [Von Hoff et al, 1990, 1992 or human promyelocytic leukemia HL-60 cells [Eckhardt et al, 1994] and amplified EGFR in human glioblastoma cells [Canute et al, 1996]. The HU treatment reduced the number of DMs in advanced ovarian carcinoma in vivo [Raymond et al, 2001].…”
Section: An Active Mechanism May Eliminate Amplifiedmentioning
confidence: 99%